Haydn composing his Creation - Kurtz:::Creator::::::::::::; Hamman, Edouard, 1819-1888 (artist):::Contributor::::::::::::
Image of Haydn sitting on a boat and looking at a storm; Lithograph by "Kurtz" based on the painting by Edouard Hamman.